Penafsiran QS Ali-Imran Ayat 102: (Analisis Tafsir Tahlili) - Putri, Nur Aprillia; Rahman, Yenni; Rizqi, Muhammad; Handayani, Rita (Institut Darul Quran Payakumbuh, 2023)
The issue of piety is a very important, in the Qur’an the word piety is 258 times in various contexts. In the book of Mu’jam the author finds one varse that discusses piety in truth, namely from the word تقاته contained in the QS. Ali-Imran verse 102. I’rab from haqqa tuqatih is maf’ul mutlaq as for its function and position as an affirmation of an action. The approach that the author uses in this study is the analysis of the tahlili method is to interpret the verses of the Qur’an systematically by describing all aspects contained in the interpreted verses. The results of the thesis research on the interpretation verses of the Qur’an systematically by describing all aspect contained in the interpreted of QS. Ali- Imran verse 102 is Allah commands his believing servants so that they truly fear him, stay on it and are steadfast until the end of their lives. The meaning of haqqa tuqatih is to carry out Allah commands by obeying Allah and not disobeying Him, remembering and not forgetting, being grateful and not disobeying, namely carrying out what Allah has commanded with earnest effort as much as possible according to the best ability. Possessions and do not take lightly what Allah has commanded. Because Allah knows whether we have tried our best in carrying out his commands or are still half hearted, and Allah will not burden us with anyting beyond our ability.